Find the equation of the tangent to the curve at te given point:

B) $f(x)=\frac{1}{\sqrt(x-1)}$ At $(2,1)$

I know the procedure on how to do it but I'm getting the wrong answer. First I found the slope and had to use binomial conjugate step, etc.

The answer is $x+2y-4=0$

  • 1
    $\begingroup$ OK, so what did you get for the derivative and the line's slope? $\endgroup$ – imranfat Feb 11 '14 at 16:41

The tangent of the curve of a function $f$ at a point $(x_0,f(x_0))$ has the equation: $$y=f'(x_0)(x-x_0)+f(x_0)$$ and in your example $f(x)=(x-1)^{-1/2}$ and $x_0=2$ hence $f'(2)=-\frac12$ so the equation is $$y=-\frac 1 2(x-2)+1\iff x+2y-4=0$$

Edited The slope of the tangent at $(2,1)$ is $$\lim_{h\to0}\frac{f(h+2)-f(2)}{h}=\lim_{h\to0}\frac{\frac{1}{\sqrt{h+1}}-1}{h}=\lim_{h\to0}\frac{(1-\sqrt{h+1})\color{red}{\times(1+\sqrt{h+1})}}{h\sqrt{h+1}\color{red}{\times(1+\sqrt{h+1})}}\\ =\lim_{h\to0}\frac{-1}{\sqrt{h+1}\color{red}{\times(1+\sqrt{h+1})}} =-\frac12$$

  • $\begingroup$ The formula is slope of tangent= (f(a+h)-f(a))/h $\endgroup$ – user127966 Feb 11 '14 at 16:46
  • $\begingroup$ And I plugged in the x value into the equation and solved and got -h^2+4h / h. Idk what to do next $\endgroup$ – user127966 Feb 11 '14 at 16:47
  • $\begingroup$ Sorry but I don't understand you. Can you explain more? $\endgroup$ – user63181 Feb 11 '14 at 16:49
  • $\begingroup$ Sorry @Sami I do not understand what you are doing. I just learned this today as I just started grade 12 calculus. Thanks for the help can you explain in more simpler/detailed terms? $\endgroup$ – user127966 Feb 11 '14 at 16:50
  • $\begingroup$ Do you know the derivative of a function? $\endgroup$ – user63181 Feb 11 '14 at 16:51

By differentiation we get:


We can then substitute $x=2$ to find the gradient of the funtion at $(2,1)$,


So the gradient is $\frac{-1}{2}$.

Now we know the slope and a point on the line, therefore we can calculate the equation of the line. The equation of a straight line is always in the form $y=mx +c$, using this fact and substituting in the gradient we just found we get:

$y=\frac{-1}{2}x+c$, luckily we also know a point on the line to substitute in to find $c$.

Using $(2,1)$:

rearranges to $c=2$ so, $y=\frac{-1}{2}x+2$
Multiplying everything by $2$ will give us: $2y=x+4$ or alternatively; $x+2y-4=0$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.